'The city's other face': Postsecular feminism and the creation of sacred space by women in Kurdish Turkey - Altay, Saadet; Clark, Jessie (Social & cultural geography, 2023)
Geographers have examined how sacred spaces are made spiritually meaningful through embodied practice. This paper brings together scholarship on post-secular feminism and geographies of religion to develop a theory of non-subversive power in the sacred space literature. This paper demonstrates how Kurdish women create sacred space through embodied Islamic mystical practices in Kurdish Turkey and how these practices carve out a space for creative existence within and alongside state and masculinist systems of power, not against. Using a post-secular feminist framing and building on conversations of power in the sacred space literature, we show how the formation of sacred space forms the feminine subject and constitutes an act of feminine agency. Specifically, we focus on two material and sacred sites: private communal prayer houses and public tomb sites used for communal petitions. In these spaces, women organize and lead collective and embodied meditations and petitions that centre their desires, concerns, and wishes in a common register to create, following Saba Mahmood, a 'politics in unusual places'.